Decolonizing Research in Education - Alexander Luis Ortiz Ocaña (Universidad del Magdalena, 2017)
In this article is characterized the genesis of it turn decolonial and is valued the possibility of developing biopraxis pedagogical decolonial. It is suggested that the configuration of other forms of research: research decolonial. Proposes a classification of types of coloniality, introducing the notions of self-coloniality and interculturality decolonial, as basic concepts in the education Research. The reflections derived from this research are concentrated on two essential aspects: the configurations in the educational sciences and dialectical relations between reality, world and human knowledge.